Comparison of allergenic extracts from different origins: the value of the FDA’s bioequivalent allergy unit (BAU) - Passalacqua, Giovanni; Pfaar, Oliver (Expert review of clinical immunology, 2016)
Introduction: Allergy immunotherapy (AIT) is the only disease-modifying intervention for the treatment of allergic diseases. The clinical effectiveness of AIT is clearly dose-dependent, so it is important that clinicians can assess and compare the potency of the various products available. However, this is not possible in practice, because manufacturers use different methods to determine potency. Therefore, a clear need exists for adoption of a ‘gold-standard’ measure of allergenicity. The bioequivalent allergy unit (BAU) is thus far the only allergen unit approved by a regulatory agency (the US Food and Drug Administration), with European regulatory authorities yet to adopt a common unit.Areas covered: Using PubMed, we performed a review of the literature on measures of allergen extract potency, use of the BAU, and BAU assessment for grass pollen tablets.Expert commentary: There is an obvious benefit to allergists and patients for having a single, comparable unit across products, and we strongly support the adoption of a single, ‘gold-standard’ unit of measurement for all products. Use of the BAU allows a clear comparison of the potency of allergen products from different manufacturers, and enables better understanding of the potential reasons for any differences in administration and dosing protocols between these products.
Gesehen am 13.02.2019